Life cycle climate change impacts of producing battery metals from land ores versus deep-sea polymetallic nodules. (1st December 2020) - Paulikas, Daina; Katona, Steven; Ilves, Erika; Ali, Saleem H.
Graphical abstract: Image 1 Highlights: Cradle-to-gate life cycle assessment of metals from land ores versus deep-sea nodules. Using nodules can reduce CO2 emissions by 80% (Ni), 76% (Cu), 29% (Co), and 22% (Mn). Nodules put 94% less sequestered carbon at risk and disrupt sequestration by 88% less. Making 1 billion EV batteries from nodules could reduce atmospheric CO2 by 11.5 Gt.